The teaching internship in action: subjects, projects, programs and perspectives in the training of the chemistry teacher - Soares, Elane Chaveiro; Moraes, Mariuce Campos de (Revista Hipótese, 2021)
We discussed the chemistry professor's formative plot, highlighting the supervised internship. We point to the advances achieved from projects and programs that have given rise to good reflections within the epistemology of professional practice, allowing us to reframe the teacher education. We recognize that the curricular restructuring for initial training is a challenge to be faced, as it articulates on the border between institutional, local and national interests that sometimes favor and sometimes belittle the idea that the teacher needs to go through a training process that prepares him for the exercise of your profession and serves as a catalyst for the continuation of this training.
Keywords: Teaching internship; Formative plot; Chemistry teaching; Pedagogical Residence